The Impact of Translation Strategies in the Children's Story “Can You Count the Stars?” A Comparative Analysis of the Quality of Two Translation Versions: Dampak Strategi Penerjemahan dalam Cerita Anak “Can You Count the Stars?” pada Kualitas Dua Versi Terjemahan: Sebuah Studi Komparatif - Larasati, Larasati; Dewi, Haru Deliana (Kementerian Sekretariat Negara Republik Indonesia, 2025)
This study examines the impact of translation strategies, including procedures, methods, and ideologies, on the quality of the rhymed children’s story “Can You Count the Stars”? (2019) translated from English into Indonesian. It aims to determine how the implementation of these strategies affects the translation quality. To address the challenges inherent in translating rhyme, such as preserving rhyme patterns, meaning, and ensuring cultural relevance. Both translators applied procedures such as modulation of perspective and meaning scope, addition, omission, and the translation of figurative language. In addition, the communicative method and a domestication ideology were applied to facilitate comprehension among child readers. The analysis shows that the translation by Respondent 1 (TSa1) demonstrates higher quality than that of Respondent 2 (TSa2), particularly in preserving rhyme patterns and delivering the message, whereas TSa2 loses some poetic nuances. Among the procedures, addition was found to be the most effective in enhancing translation quality by enriching the text without distorting the message. This study concludes that the careful selection and application of translation strategies play a critical role in balancing rhyme, meaning, and cultural context in rhymed children’s literature and support previous research on the significance of strategy selection in achieving quality translations.